Test of Some Concentration of Piper Aduncum L. Fruit Flour Extract to Control Nettle Caterpillar Setora nitens Walker (Lepidoptera;limacodidae) at Oil Palm of Plant (Elaeis guineensis jacq) - Rudi Gunarso; Rusli Rustam; Jeltje Hennie Laoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Nettle Caterpillar Setora nitens is a major pest on oil palm. Chemical control to nettle caterpillar Setora nitens has some negative impacts, such as pest resistance, pest resurgence, and environmental pollution. The use of botanical insecticides, such as Piper aduncum L. is one of solutions to decrease the use of synthetic chemical insecticides. The purpose of this research is to obtain the concentration of Piper aduncum L. fruit flour extract which is able and exact to control nettle caterpillar Setora nitens pest at the oil palm plant. This research was conducted in field using Completely Randomized Design (CRD) with 5 treatments and 4 repetitions. The treatment concentrations of Piper aduncum L. fruit flour extract are 0 g/l of water, 25 g/l of water, 50 g/l of water, 75 g/l of water, and 100 g/l of water. The Piper aduncum L. fruit flour extract concentration 100 g/l of water is able to control nettle caterpillar Setora nitens pest with total mortality of 85%. The exact concentration needed to kill 95% nettle caterpillar Setora nitens pest is 32,1% or equivalent to 321 g/l of water. However, it is not yet effective because the effective and exact concentration to kill 95% of insect test more than 10% or equivalent to 100 g/l of water. Keyword: Oil Palm (Elaeis guineensis Jacq), Nettle Caterpillar Setora nitens Walker, Piper aduncum L.